1st Independent Steering Committee Meeting, 26 April 2017 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
In April 2017 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its first Independent Steering Committee meeting.